Distribution of Bombus haemorrhoidalis Smith and its Interrelationship with Host Plants in Chitwan Annapurna Landscape of Central Nepal - Ghimire, Kishor Chandra; Bhusal, Daya Ram (BMC Journal of Scientific Research, 2021)
Occurrence and variety of flowering host plant of native Bombus pollinators are viewed as basic alternatives than the imported species. The use of native bumblebee species for pollination was considered more significant than imported bumblebees to reduce environmental impact and pest problems. B. haemorrhoidalis is the most dominant species of Chitwan Annapurna Landscape in agricultural and wild flora during April to September 2019. We followed assessable walking trails and used insect net for sample collection. The effect of different environmental variables on the floral host plant resources of this native bumblebee was examined. With eight locations ranging from 1407 to 2506 meters above sea level, twenty-seven species of seventeen plant families were identified as pollen and nectar foraging host plants. B haemorrhidalis distribution frequency is correlated with relative humidity (0.07438968) and altitude (0.495657857). The most visited plant family was Balsaminaceae and plant was Imatian scrabida. This study gives the knowledge of abundance of host plants, ecological and biological relationship of the B. haemorrhoidalis in Nepal